The Effects of 2 μG and 4 μG Doses of Dexmedetomidine in Combination with Intrathecal Hyperbaric Bupivacaine on Spinal Anesthesia and its Postoperative Analgesic Characteristics - Abdulkadir Yektaş; Enver Belli (Pain Research and Management)
OBJECTIVE: To compare the postoperative analgesic characteristics and side effects of two different doses of intrathecal dexmedetomidine in combination with hyperbaric bupivacaine, and to evaluate the effects of these combinations on spinal anesthesia.